(untitled) (Research, Society and Development, 2022)
Brazil, to meet the goals established in the Paris Agreement in 2015, created the RenovaBio Program in 2017, in which the country’s first official carbon credit (CBIO) was also established, which is traded on the Stock Exchange (B3). As the topic is very recent, it was necessary to understand how this type of negotiation happens and what the requirements and agents it involves. Therefore, the objective of this work was: 1) to carry out a narrative literature review to address the need to understand the credit negotiation model and 2) to bring historical data on average prices, negotiated volume and financial movement of CBIOs over the period of June from 2020 to December 2021, along with technical and fundamental analysis to explore the reasons for price swings. The main result of the bibliographic review was an explanatory framework of the CBIOs negotiation system, which allowed a clear understanding of how it occurs. The results of the analyzes allowed the perception that as the retirement period of CBIOs approached - the last day of each year, 2020 and 2021 respectively - the unit values ​​of credit went up. It was concluded that the study carried out in this article solved the problem of understanding on the subject, as well as it was important to bring some reasons for price fluctuations through technical and fundamental analysis, which allowed us to understand the dynamics of the CBIOs market.